Biochar of Prosopis juliflora for Improving Crops Germination and Growth on Sandy–Loam Soil - Jamal Ali; Ali Seid Mohammed; Amare Bitew Mekonnen (Advances in Agriculture)
Prosopis juliflora (Sw.) DC. is an invasive alien species (IAS) damaging agricultural and natural ecosystems that threat biodiversity in Ethiopia. This IAS can be managed by utilizing it as a resource in agricultural production. This study analyzed the role of P. juliflora biochar on germination and growth performance of maize and wheat under field conditions in Wollo, Ethiopia. A randomized complete block design (RCBD) was used to test the effect of biochar on sandy–loam soil with and without fertilizer. In this experiment, biochar from P. juliflora was applied on the above two crops at 5, 10, and 20 t/ha with and without N–P fertilizers. From the result, a 100% germination and high growth of test crops were observed from 10 t/ha biochar with fertilizer mixed treatments. The shoot dry weight of both maize and wheat showed significant differences among treatments. While a single dosage (10 t/ha) increased maize dry weight by 21% without fertilizer, but it reduced dry weight by 10% when used with fertilizer. In the case of wheat, single and double dose biochar with NPS treatments increased shoot dry weight by 22.2% and 30%, respectively. This showed that application of biochar up to 20 t/ha in combination with fertilizers can significantly improve crop growth. Thus, it can be concluded that the application of biochar of P. juliflora is a good soil amendment option and, thus, this IAS can be managed by utilization.